2020
DOI: 10.1186/s12883-020-01944-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolated leptomeningeal angiomatosis in the sixth decade of life, an adulthood variant of Sturge Weber Syndrome (Type III): role of advanced Magnetic Resonance Imaging and Digital Subtraction Angiography in diagnosis

Abstract: Background Sturge-Weber syndrome (SWS) is primarily diagnosed in pediatric population, but clinical presentation in late adulthood is rarely reported. Evolution of radiological findings in the adulthood variant of SWS with isolated leptomeningeal angiomatosis has never been reported to our knowledge. Case presentation We report here a case of an isolated temporo-parieto-occipital leptomeningeal angiomatosis on the right cerebral hemisphere in a sixty-two-year-old male who presented with generalized seizure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[1][2][3][4] It is very rarely seen in later life. 5 It is believed to be caused by abnormal persistence of embryonic venous plexus near the ectoderm that was destined to form venous drainage of the occipital and parietal region of the brain and facial skin. 3,4 The low-flow angiomata in SWS are at risk of thrombosis and calcification, which eventually lead to ischemia and gliosis of surrounding nervous tissue and atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4] It is very rarely seen in later life. 5 It is believed to be caused by abnormal persistence of embryonic venous plexus near the ectoderm that was destined to form venous drainage of the occipital and parietal region of the brain and facial skin. 3,4 The low-flow angiomata in SWS are at risk of thrombosis and calcification, which eventually lead to ischemia and gliosis of surrounding nervous tissue and atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are few cases reported that have been diagnosed at a later age. 5 Brain MRI without contrast may not show leptomeningeal angioma at times, and contrast imaging is very important in patients suffering from seizures to achieve a good diagnosis. 2,4,5 Cerebral calcifications can be seen on brain MRI in patients with encephalitis, purulent meningitis, celiac disease, leukemia, and ossifying meningoencephalopathy, and hence, appropriate investigations including CSF analysis and cerebral angiography are advised.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations